2020
DOI: 10.1016/j.jse.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

SECEC Grammont Award 2017: the prejudicial effect of greater tuberosity osteotomy or excision in reverse shoulder arthroplasty for fracture sequelae

Abstract: Hypothesis: The aim was to evaluate risk factors for complications, revision, and mid-to long-term outcomes after reverse shoulder arthroplasty (RSA) implanted for proximal humeral fracture sequelae (PHFS). Methods: The radiographs of 98 patients (mean age, 68 years) who underwent RSA for the treatment of PHFS were reviewed at a minimum 5-year follow-up. PHFS were divided into 4 types according to the Boileau classification: type 1 (46 cases), type 2 (6 cases), type 3 (12 cases), and type 4 (34 cases). The tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“… 14 In this latter case, should the patient undergo rTSA, an accurate placement of the stem could be technically difficult with a high rate of complications. 6 , 8 , 18 , 22 In order to correct humeral deformities without performing an osteotomy of the greater tuberosity, Neer recommended to ream eccentrically the medullary canal and to use an undersized humeral stem placed in a nonanatomic position. 21 Conversely, other authors have proposed to use stemless or onlay stem prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 14 In this latter case, should the patient undergo rTSA, an accurate placement of the stem could be technically difficult with a high rate of complications. 6 , 8 , 18 , 22 In order to correct humeral deformities without performing an osteotomy of the greater tuberosity, Neer recommended to ream eccentrically the medullary canal and to use an undersized humeral stem placed in a nonanatomic position. 21 Conversely, other authors have proposed to use stemless or onlay stem prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported an intraoperative fracture rate between 6.8% and 33%. 6 , 19 , 25 , 26 In a review including 9 studies and 234 patients affected by PHFS (without any distinction about subtype) treated with rTSA, Holton et al reported a 29% rate of severe complication (dislocation in 16.7%, infection in 6.8%, periprosthetic fracture in 3%, and nerve injury in 2.6% of cases) . 14 In 2020, Boileau et al reported the results achieved in 98 patients presenting with PHFS, undergone rTSA and followed at a minimum of 5 y.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations